2016
DOI: 10.1016/j.jcjo.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Retrobulbar hemorrhage and prasugrel

Abstract: Retrobulbar hemorrhage and prasugrelRetrobulbar hemorrhage (RBH) is the accumulation of blood in the orbit behind the globe. Although some hemorrhages are minor and do not result in significant mass effect, an RBH is an ophthalmologic emergency requiring immediate surgical intervention. An RBH manifests as acute ipsilateral orbital pain and proptosis and can be variably associated with loss of vision, ophthalmoplegia, subconjunctival hemorrhage, and increased intraocular and intraorbital pressure. 1 Most cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
3
0
2
Order By: Relevance
“…Los principales signos clínicos de esta patología son proptosis, dolor ocular, disminución de agudeza visual, oftalmoplejia, resistencia a la retropulsión ocular, quemosis conjuntival, edema de papila, congestión venosa e isquemia retiniana 1 , 4 . La sospecha rápida inicial es fundamental, puesto que el diagnóstico es clínico.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Los principales signos clínicos de esta patología son proptosis, dolor ocular, disminución de agudeza visual, oftalmoplejia, resistencia a la retropulsión ocular, quemosis conjuntival, edema de papila, congestión venosa e isquemia retiniana 1 , 4 . La sospecha rápida inicial es fundamental, puesto que el diagnóstico es clínico.…”
Section: Discussionunclassified
“…La hemorragia retrobulbar consiste en el sangrado en la región intraorbitaria retroseptal. Al encontrarse entre los huesos orbitarios y el propio septo orbitario, es una región poco distensible; por ello se genera un síndrome compartimental en el que, sin una resolución quirúrgica urgente, la isquemia mantenida de los tejidos intraorbitarios más nobles provocará una pérdida visual irreversible 1 .…”
Section: Introductionunclassified
“…Son et al reported that anticoagulants, though not acetylsalicylic acid, significantly increase the risk of retrobulbar hemorrhage [ 11 , 12 ]. Contrarily, Matharu et al [ 13 ] reported a case of retrobulbar hemorrhage in a patient on dualantiplatelet therapy (acetylsalicylic acid and prasugrel). The authors emphasized the importance of investigating the medical history for antithrombotic agent usage in patients with orbital fractures or retrobulbar injections [ 11 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Contrarily, Matharu et al [ 13 ] reported a case of retrobulbar hemorrhage in a patient on dualantiplatelet therapy (acetylsalicylic acid and prasugrel). The authors emphasized the importance of investigating the medical history for antithrombotic agent usage in patients with orbital fractures or retrobulbar injections [ 11 , 13 ]. However, our patient did not have such a medical history.…”
Section: Discussionmentioning
confidence: 99%
“…She presented for panretinal photocoagulation under retrobulbar block but she developed retrobulbar hemorrhage. Newer, more potent Aptl drugs might carry higher risks of severe bleeding complications in susceptible patients ( 18 ). Anesthesiologists and ophthalmologists should consider delay of the surgery until dual Aptl therapy is no longer needed, to hold prasugrel or avoid retrobulbar blocks and choose different regional ophthalmic blocks such as peribulbar block with the use of ultrasound.…”
Section: Discussionmentioning
confidence: 99%